AeMg6Ga6S16 (Ae = Ca, Sr, Ba): The First Double Alkaline‐Earth Metal Chalcogenides with Excellent Performances. Issue 2 (24th November 2022) - Chen, Jiale; Zhang, Yujie; Wu, Hongping; Hu, Zhanggui; Wang, Jiyang; Wu, Yicheng; Yu, Hongwei
Abstract: Infrared nonlinear optical (IR NLO) crystals are of quite significance in the development of laser technology, yet rationally designing new IR NLO crystal that can satisfy all the property requirements is still a great challenge owing to the incompatibility between large second harmonic generation (SHG) response and wide band gap. Herein, taking AgGaS2  (AGS) as the template and using highly electropositive alkaline‐earth metal cations substituting Ag + cations, the first examples of double alkaline‐earth (Ae) metal chalcogenide IR NLO crystals, AeMg6 Ga6 S16 (Ae = Ca, Sr, Ba), are successfully designed and synthesized. Structurally, they possess stable [Mg/GaS]∞ open frameworks, which can accommodate a wide range of cations from the small size of Ca 2+ to large Ba 2+ cations and all of the resulting compounds melt congruently. More importantly, these materials achieve the optimal balance among the critical performance parameters, including the strong SHG response (≈0.7–0.8 × AGS) and wide band gap ( Eg  = 3.50–3.54 eV). Theoretical calculations and structure analysis reveal that their superior NLO properties can be attributed to the synergistic contribution of the polarizable MgS6 and GaS4 groups. Abstract : Based on the chemical substitution and Mg‐octahedra coupling single/double chains strategy, the first examples of double alkaline‐earth (Ae) metal chalcogenide infrared nonlinear optical (IR NLO) crystals, AeMg6 Ga6 S16 (Ae = Ca, Sr, Ba), are successfully synthesized and exhibit well‐balanced IR NLO properties, including large phase‐matchable second harmonic generation responses, wide band gaps, high laser‐induced damage thresholds, and moderate birefringences.